APAKAH CORPORATE GOVERNANCE DAN FINANCIAL PERFORMANCE DAPAT MEMODERASI PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP FIRM VALUE? - Natalie, Vanessa; Eriandani, Rizky; Rudiawarni, Felizia Arni (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2023)
This study aims to examine the effect of CSR on Firm Value (FV) and analyze whether Good Corporate Governance (GCG) and Financial Performance can strengthen or weaken this influence. This study uses data on non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2019–2021 with a total sample of 1048 firm years. Data analysis using multiple linear regression. CSR measurement using content analysis. Firm Value is measured using Stock Return. GCG is measured using Board Size (BS), Board Independence (B-IND), Family Ownership (FMO), and Largest Ownership (L-OWN). Financial Performance proxies use Return on Assets (ROA) and Net Profit Margin (NPM). Empirical results show that CSR has a positive effect on Firm Value. Financial Performance (ROA) weakens the relationship between CSR and FV. However, GCG is unable to moderate the relationship between CSR and FV. This research confirms that CSR activities are essential to increase firm value and business sustainability.